Environmental Protection as a Legal Obligation in Islamic Law: A Thematic Study of the Qur'an and Hadith - Muklis Siregar; Muzakkir Muzakkir; Sulidar Sulidar (Universitas Muhammadiyah Tangerang, 2025)
The environmental crisis in the form of natural disasters (flash floods) that occurred in several areas in Sumatra (West Sumatra, North Sumatra, and Aceh) at the end of this year has once again reminded us that Indonesia is a country highly vulnerable to hydrometeorological disasters. These events not only caused physical damage but also left trauma and profound loss for the community, including homes, jobs, and families. In facing this crisis, a spiritual approach through religious teachings, particularly Islam, is crucial. The Qur'an not only teaches ritual worship but also contains the principle of natural balance (mÄ«zÄn) and the prohibition of destroying the earth. This study aims to examine the concept of natural balance from a Qur'anic perspective through a thematic interpretation approach, as well as to analyze its relevance and implications for modern life. Using a qualitative method based on literature, this article examines Qur'anic verses related to environmental themes, the role of humans as caliphs, and ethical values in protecting the environment. The results of the study show that the Qur'an explicitly emphasizes the importance of maintaining environmental balance as part of the caliph's mandate on earth. The imbalance that occurs due to excessive exploitation and environmental damage constitutes a violation of divine values. In the context of modern life, these values are highly relevant as a foundation for ecological ethics in addressing the global environmental crisis. Therefore, strengthening spiritual awareness based on the Quran is crucial for developing an environmentally friendly and sustainable lifestyle.